Tramadol and Dexamethasone as Adjuvant to Bupivacaine in Supraclavicular Brachial Plexus Block - Shrutika Ved; Neel Rana; Shruti Shah; Ruchi Shah; Ishitaben Gajipara; Mrugakshi Dave (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Background: To assess the effects of combining Tramadol and Dexamethasone with Bupivacaine in supraclavicular brachial plexus block for upper limb surgeries. Material and Methods: A clinical research was performed with sixty patients who received upper limb surgery with a supraclavicular brachial plexus block. The study encompassed a total of 60 patients who were divided into two groups, with 30 patients in each group. Group D was administered a blend of Bupivacaine and Dexamethasone, whilst Group T was given a mixture of Bupivacaine and Tramadol, resulting in a combined amount of 25 ml. The study recorded the beginning and length of the sensory and motor block. We meticulously observed the hemodynamic variables throughout the research, until the administration of the first rescue analgesic. Results: In group D, the mean time for motor block to occur was 5.10±0.92 minutes, whereas in group T, it took 7.93±0.98 minutes. Group D had an average sensory block onset time of 8.23±1.22 minutes, whereas Group T had a slightly longer average onset time of 10.97±1.22 minutes. Group D had an average motor block duration of 560.53±24.46 minutes, whereas group T had a duration of 358.93±20.85 minutes. Group D had a mean duration of sensory block of 745.17±32.81 minutes, whereas group T had a slightly shorter duration of 457.07±16.36 minutes. In group D, the average time for the first rescue analgesia was 961.50±32.94 minutes, whereas in group T, it was 524.17±16.46 minutes. Conclusion: Inclusion of Dexamethasone led to a noticeably quicker onset of motor and sensory block in comparison to Tramadol. In a recent study, researchers discovered that when Dexamethasone was added to the mix, it had a notable impact on the duration of both motor and sensory block. The effects were significant and promising. When Dexamethasone was added, it noticeably increased the duration until the first rescue analgesia, in comparison to Tramadol.